Revisiting the Two-Step Flow Model on Twitter: Interconnection of Self-Identified South Korean Twitter Opinion Leadership, News Consumption, News Links, and News Curation. (June 2019) - Park, Chang Sup
This study compares the news consumption, sharing and curating behavior on Twitter between Twitter opinion leaders and traditional opinion leaders, based on an online survey of 1, 005 South Korean adults. The results indicate that both traditional opinion leadership and Twitter opinion leadership are significantly related to a high level of news use via traditional media and social networking sites (SNS). While traditional opinion leaders are likely to add links of traditional media news and web-only sites news to their tweets, Twitter opinion leaders tend to add links of traditional media news, web-only sites news, SNS news, and citizen journalism news to their tweets. This study also finds that those who consume news and curate the news on Twitter reveal stronger Twitter opinion leadership than those who consume news but do not curate the news.